RUNOFF VARIABILITY IN THE SCOTT RIVER (SW SPITSBERGEN) IN SUMMER SEASONS 2012–2013 IN COMPARISON WITH THE PERIOD 1986–2009 - Franczak, Łukasz; Kociuba, Waldemar; Gajek, Grzegorz (Quaestiones Geographicae, 2016)
River runoff variability in the Scott River catchment in the summer seasons 2012 and 2013 has been presented in comparison to the multiannual river runoff in 1986–2009. Both in particular seasons and in the analysed multiannual, high variability of discharge rate was recorded. In the research periods 2012–2013, a total of 11 952 water stages and 20 flow rates were measured in the analysed cross-section for the determination of 83 daylong discharges. The mean multiannual discharge of the Scott River amounted to 0.96 m3·s–1. The value corresponds to a specific runoff of 94.6 dm3·s–1·km2, and the runoff layer 937 mm. The maximum values of daily discharge amounted to 5.07 m3·s–1, and the minimum values to 0.002 m3·s–1. The highest runoff occurs in the second and third decade of July, and in the first and second decade of August. The regime of the river is determined by a group of factors, and particularly meteorological conditions affecting the intensity of ablation, and consequently river runoff volume. We found a significant correlation (0.60 in 2012 and 0.67 in 2013) between the air temperature and the Scott River discharge related to the Scott Glacier ice melt.